Relación entre signos y síntomas de desordenes temporo-mandibulares y disarmonias oclusales en estudiantes de Odontología de la UNMSM - Arrollo Pérez, Carlos Alberto (2001)
A clinical research was relized wirt the purpose to reloation TTM simptoms and occlusal discrepancy. 205 students of dentistry belonging to the Universidad Nacional Mayor de San Marcos (UNMSM Lima-Perú), male and female, with 22 years old as middle, was interrogated and examined to value articular sound and pain (articular and/or muscular origin); besides the Peter Dawson's technique was used to detect the occlusal discprepancy. The results was analyse through the programs EPI INFO 6.0 and SPSS(FW)the results shows: A prevalence 46.8% of TTM. Significant results between: TTM sympton and nonworking side interference TTM sympton and cross bite TTM sympton and dental attrition (temporal and masseter) TTM sympton wasgrowing accord to academic oeriod, maybe anxiety play an important rol in these disorders.